Evaluasi Implementasi SIPD dalam Pengelolaan Keuangan Daerah pada BKAD Kota Palangka Raya - Aditya Rahmadani; Achmad Syamsudin; Helma Prasetya Sanjaya (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study aims to evaluate the implementation of the Regional Government Information System of the Republic of Indonesia (SIPD RI) in regional financial management at the Regional Finance and Asset Agency (BKAD) of Palangka Raya City. This research uses a descriptive qualitative approach, with data collected through interviews, observation, and documentation. The analysis was conducted using Edward III’s theory, which includes communication, resources, disposition, and bureaucratic structure. The results show that SIPD RI has supported the processes of planning, budgeting, administration, reporting, and regional asset management. However, its implementation still faces several obstacles, including delays in information delivery, limited employee competence, network disruptions, server errors, and dependence on certain operators. Therefore, SIPD RI has been implemented fairly well, but it still requires strengthening in terms of training, infrastructure, and technical coordination.